Vitamin A deficiency in the MENA region: a 30-year analysis (1990–2019) - Safiri, Saeid; Mousavi, Seyed Ehsan; Nejadghaderi, Seyed Aria; Motlagh Asghari, Kimia; Karamzad, Nahid; Sullman, Mark J. M.; Kolahi, Ali-Asghar; Abdollahi, Morteza (Frontiers in Nutrition, 2024)
Background: Vitamin A deficiency (VAD) is a common micronutrient deficiency that imposes a substantial burden worldwide. The Thispresent study aimed examinedto report the burden of VAD from 1990 to 2019 in the Middle East and North Africa (MENA) region by age, sex and sociodemographic index (SDI).The data were obtained from the Global Burden of Disease (GBD) 2019 database. We reported the prevalence, incidence, and years lived with disability (YLDs) that were attributable to VAD for the MENA region, along with and its constituent countries.In 2019, there were MENA region had 30.6 million prevalent cases in MENAof VAD, with an age-standardised prevalence rate of 5249.9 per 100000 population. In addition, VAD was responsible for 62.2 thousand YLDs, with an age-standardised YLD rate of 10.2 per 100000 population. The age-standardised prevalence [50.3% (-55.9 to -44.7)] and YLD [-49.3% (-55.3 to -43.1)] rates of VAD have significantly decreased since 1990. In 2019, the MENA region's VADattributable YLD rate was lower belowthan the global average for males and females across all age groups. FurthermoreAdditionally, SDI was negatively associated the age-standardised YLD rate of VAD was negatively associated with SDI.This study underscores the necessity of frequently updating health data and developing, guidelines and regulations to prevent, detect early, and effectively treat VAD in the MENA countries.